Pengaruh Model Pembelajaran dan Kreativitas Siswa Terhadap Hasil Belajar Sejarah di SMA Islam Al-Azhar 8 Summarecon - Wahyudin Wahyudin (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
This study aimed to find out the effect of Instructional model and student creativity towardthe learning outcome of student history in SMAI Al-Azhar 8 Summarecon. The approach used wasquantitative with treatment design by level 2x2 experiment method. The study populations were thewhole of eleventh grade students and for the sample consist 2 classes, social student 2 of eleventhgrade and social student 3 of eleventh grade amount 68 students. This study instrument used thatused for the student creativity was quiz and for the learning outcome was multiple choice. The surveyresults revealed: (1) the learning outcome that used TAI instructional model was higher than theconventional instructional model, (2) there was effect of interaction between learning model andcreativity, (3) the learning outcome of student history that used TAI learning model with highcreativity result revealed higher than the conventional learning model, (4) the learning model ofstudent history with low creativity result revealed lower than the conventional learning model.